Neoadjuvant treatment strategies for resectable pancreas cancer: A propensity-matched analysis of the National Cancer Database. (February 2020) - Xiang, Michael; Heestand, Gregory M.; Chang, Daniel T.; Pollom, Erqi L.
Highlights: The optimal neoadjuvant treatment in resectable pancreas cancer is unclear. Chemotherapy alone, with conventional RT, or with SBRT were compared. Neoadjuvant SBRT was associated with favorable survival and pathological outcomes. Combination of full-dose chemotherapy and SBRT warrants prospective study. Abstract: Background and purpose: The optimal neoadjuvant approach in patients with resectable pancreas cancer is unclear. We investigated outcomes after preoperative chemotherapy alone, chemotherapy with conventionally-fractionated radiation (CFRT), or chemotherapy with stereotactic body radiotherapy (SBRT). Materials and methods: The NCDB was queried for patients with resectable pancreatic adenocarcinoma (pretreatment stage T1-3, N0-1, M0) who received preoperative, multiagent chemotherapy and definitive surgery from 2010 to 2015. CFRT was 40–60 Gy in 20–35 fractions. SBRT was 20–25 Gy in 1 fraction or 30–50 Gy using at least 5 Gy per fraction. Multivariable regression and propensity score matching were used to adjust for potential confounders, including age, comorbidity score, and pretreatment extent of disease. The primary outcome was overall survival measured from surgery. Results: In total, 1355 patients received preoperative chemotherapy alone, 552 patients received preoperative chemotherapy with CFRT, and 175 patients received preoperative chemotherapy with SBRT. Receipt of SBRT was associated with significantly improved overall survival compared to chemotherapy alone (median 30 vs 21 months, p = 0.02; adjusted hazard ratio [HR] 0.65, 95% confidence interval [CI] 0.47–0.90, p = 0.01). Similarly, SBRT was associated with significantly improved overall survival compared to CFRT (median 29 vs 16 months, p = 0.002; adjusted HR 0.53, 95% CI 0.37–0.76, p = 0.001). Additionally, SBRT was associated with significantly increased rates of pathological complete response and margin-negative resection. Rates of postoperative readmissions and mortality were comparable. Conclusions: Neoadjuvant chemotherapy with SBRT is associated with favorable survival and pathological outcomes, warranting consideration for prospective validation.